1992
DOI: 10.1002/ijc.2910510411
|View full text |Cite
|
Sign up to set email alerts
|

Immunorecognition of different ganglioside epitopes on human normal and melanoma tissues

Abstract: There is increasing evidence that cell-surface gangliosides play a role in tumor growth, progression and metastases. In order to determine the frequency of ganglioside GD3 in patients with metastatic malignant melanoma for further therapeutic trials, GD3 ganglioside expression was determined in 119 tissue samples. Of these melanomas, 93% (111/119) were R-24-positive, which indicates the value of this diagnostic marker for melanoma. To study the structural epitopes of gangliosides, 10 ganglioside antibodies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…9-O-acetyl-GD3 has been reported to be present in granulocytes and T lymphocytes by Kniep et al (1993) but was not observed in our study in any normal tissues except for weak expression in connective tissue of prostate and ovary, making it a good target for immune attack against melanoma. GD3 and GD2 expression on melanomas, neuroblastomas and sarcomas (Hamilton et al, 1993a,b;Dippold et al, 1985;Cheung et al, 1985), the expression of GD3 in normal brain and connective tissue elements as well as islet cells of the pancreas and the expression of GD2 in brain and connective tissue elements in a variety of organs have all been described before Bernhard et al, 1992;Cheung et al, 1985). However, the presence of GD2 in splenic white pulp, lymph node germinal centers and B cell lymphomas was unexpected and raises the possibility of using GD2 as a target against B cell lymphomas.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…9-O-acetyl-GD3 has been reported to be present in granulocytes and T lymphocytes by Kniep et al (1993) but was not observed in our study in any normal tissues except for weak expression in connective tissue of prostate and ovary, making it a good target for immune attack against melanoma. GD3 and GD2 expression on melanomas, neuroblastomas and sarcomas (Hamilton et al, 1993a,b;Dippold et al, 1985;Cheung et al, 1985), the expression of GD3 in normal brain and connective tissue elements as well as islet cells of the pancreas and the expression of GD2 in brain and connective tissue elements in a variety of organs have all been described before Bernhard et al, 1992;Cheung et al, 1985). However, the presence of GD2 in splenic white pulp, lymph node germinal centers and B cell lymphomas was unexpected and raises the possibility of using GD2 as a target against B cell lymphomas.…”
Section: Discussionmentioning
confidence: 87%
“…It has been difficult to select optimal antigens and tumor targets based on these previous studies. The distribution of the antigens studied here has been described (Dippold et al, 1985;Bernhard et al, 1992;Cheresh et al, 1984;Brezicka et al, 1989;Bremer et al, 1984;Husmann et al, 1990), but the number and types of tissues studied were generally limited and involved MAbs against one or two antigens without comparison with the expression of other antigens. For this reason, we have begun a large immunohistochemical study on frozen tissue sections of tumor and normal tissues using a panel of well-characterized murine MAbs against a series of these candidate antigens.…”
Section: Wiley-liss Incmentioning
confidence: 92%
See 1 more Smart Citation
“…In summary, whereas previous workers have recognized that the antigenicity and immunogenicity of gangliosides and other glycosphingolipids depends on the density of the antigen on the cell surface, the chain length of the fatty acids and their ␣ -hydroxylation, and the cryptic behavior of glycosphingolipids (Hakomori 1986), the present study demonstrates that the method of fixation is vitally important for unambiguous conclusions to be drawn about the localization of a ganglioside in biological tissues using anti-ganglioside antibodies. This is of importance not only for localizing gangliosides in biological tissues (Schwarz and Futerman 1996) but also for using anti-ganglioside antibodies as diagnostic tools (Bernhard et al 1992;Lloyd et al 1992). …”
Section: Discussionmentioning
confidence: 99%
“…KM641 was chosen from ten mouse anti-GD3 mAb on these criteria in this study. Several anti-GD3 mAb have been produced so far [2,5,7,14,15,25,27,36,37] and R24 is the only well-studied and clinically used anti-GD3 mAb among them. The binding specificity of KM641 was almost the same as that of R24 in that the both mAb had weak cross-reactivity with GQlb [2,36].…”
Section: Discussionmentioning
confidence: 99%